Aktivitas dan Kreativitas Siswa pada Penerapan Metode Tasmuco (Talking Stick Music With Combination) dengan Pendekatan Open-ended - Nur Islamiati; Muh. Irfan; Yeni Rahmawati; Muhammad Wahyu Setiyadi (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
This study aims to describe student learning activities and creativity in the application of the TASMUCO learning method (talking stick music with combination) with an open-ended approach. The research approach used in this study is a quantitative and qualitative approach with a description type. The research subjects were 28 students at MTs Yasim Nata. The data generated by using a questionnaire with a Likert scale type. This can be seen from the results of the analysis of student activity data, which obtained an average score of 3.41 with a good category. As for the results of the data analysis of student creativity, the overall average value of all indicators obtained an average of 3.21 with a good category. This shows that the application of the TASMUCO learning method (talking stick music with combination) with an open ended has a positive impact on student learning activities and creativity. So it is recommended for educators to use innovative methods in learning such as TASMUCO (talking stick music with combination) with an open-ended approach.